Carer‐related research and knowledge: Findings from a scoping review. (30th May 2018) - Larkin, Mary; Henwood, Melanie; Milne, Alisoun
Abstract: The review discussed in this paper provides a unique synthesis of evidence and knowledge about carers. The authors adopted a scoping review methodology drawing on a wide range of material from many different sources published between 2000 and 2016. It offers key insights into what we know and how we know it; reinforces and expands evidence about carers' profile; shows knowledge is uneven, e.g. much is known about working carers, young carers and carers of people with dementia but far less is about older carers or caring for someone with multiple needs. A striking feature of much research is a focus on caring as a set of tasks, rather than a dimension of an, often dyadic, relationship. While there is substantive evidence about the negative impact of caring, the review suggests that links between caring and carer outcomes are neither linear nor inevitable and vary in depth and nature. A reliance on cross‐sectional studies using standardised measures is a major weakness of existing research: this approach fails to capture the multidimensionality of the caring role, and the lived experience of the carer. Although research relating to formal support suggests that specific interventions for particular groups of carers may be effective, overall the evidence base is weak. There is a tension between cost‐effectiveness and what is valued by carers. Developing robust evaluative models that accommodate this tension, and take account of the dyadic context of caring is a critical challenge. A fundamental deficit of carer‐related research is its location in one of two, largely separate, paradigmatic frameworks: the "Gatherers and Evaluators" and the "Conceptualisers and Theorisers." The authors suggest that developing an integrated paradigm that draws on the strengths and methods of existing paradigms, has considerable potential to generate new knowledge and new evidence and extend understanding of care and caring.